2019
DOI: 10.1371/journal.pone.0216622
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways for the formation of the γ-glutamyl peptides γ-glutamyl-valine and γ- glutamyl-valyl-glycine in Saccharomyces cerevisiae

Abstract: The role of glutathione (GSH) in eukaryotic cells is well known. The biosynthesis of this γ-glutamine tripeptide is well studied. However, other γ-glutamyl peptides were found in various sources, and the pathways of their formation were not always clear. The aim of the present study was to determine whether Saccharomyces cerevisiae can produce γ-glutamyl tripeptides other than GSH and to identify the pathways associated with the formation of these peptides. The tripeptide γ-Glu-Val-Gly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Of the potential kokumi-tasting compounds, some of the γ-glutamyl peptides, calcium, and the biogenic amine spermidine exhibited the lowest EC 50 values for cCaSR. The formation of γ-glutamyl peptides is linked to GSH metabolism, and both γ-glutamyl peptides and GSH are found in different meats 32 , 33 , meaning that these compounds are present in a carnivorous diet. Similarly, spermidine, which is a biogenic amine, is found in food sources palatable to cats, including chicken liver 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the potential kokumi-tasting compounds, some of the γ-glutamyl peptides, calcium, and the biogenic amine spermidine exhibited the lowest EC 50 values for cCaSR. The formation of γ-glutamyl peptides is linked to GSH metabolism, and both γ-glutamyl peptides and GSH are found in different meats 32 , 33 , meaning that these compounds are present in a carnivorous diet. Similarly, spermidine, which is a biogenic amine, is found in food sources palatable to cats, including chicken liver 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, GCL presents a relatively broad substrate specificity and can bind glutamate with some other amino acids in addition to cysteine, producing the corresponding γ-glutamyl dipeptides [77]. The role of γ-glutamyl dipeptides in cells is not yet fully understood, but they have been detected in both the brain and eyes [78], indicating a potential involvement of these compounds in neuronal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The lower amount of GCLC and/or the lower GSH substrate availability to γ-glutamyltransferase, responsible for the transfer of the γ-glutamyl moiety to any amino acid [78], may thus account for the lower amount of the γ-glutamyl-tyrosine dipeptide detected in the CM of hSOD1(G93A) astrocytes by the metabolomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serine palmitoyl transferase will also metabolize alanine or glycine when serine is limiting (Penno et al, 2010) and glutamate-aspartate aminotransferase will also metabolize cysteine sulfinic acid (Weinstein et al, 1988). In the case of GCLC, this feature may have been selected for during evolution, as the S. cerevisiae homolog (Gsh1p) also has the ability to at least use valine (Sofyanovich et al, 2019). Additional work is needed to determine which other amino acids are accepted by S.…”
Section: Discussionmentioning
confidence: 99%
“…However, 13 C5, 15 N2-glutamine tracing demonstrated that while the newly labeled GSH fraction was very small, as expected, glutamate and γ-glutamyl-dipeptides were newly labeled to ~ 50% in cystine starved A549 cells ( Figure 4C and D), suggesting that the γ-glutamyl dipeptides were synthesized from glutamate but not from GSH ( Figure S4B). Because γ-glutamyl-valine is synthesized by the Saccharomyces cerevisiae glutamate-cysteine ligase (Sofyanovich et al, 2019), and γ-glutamyl dipeptide synthesis by mouse liver extracts was recently shown to be GCLC-dependent (Kobayashi et al, 2020), we hypothesized that the γ-glutamyl dipeptides were directly generated by GCLC rather than GSH metabolism by GGT. To evaluate this, we evaluated the γ-glutamyl dipeptide levels in the GCLC and GSS KO clones.…”
Section: γ-Glutamyl Peptide Synthesis By Gclc Scavenges Glutamate To mentioning
confidence: 99%